Ni self-diffusion in glass forming Pd–Ni–S melts. (18th August 2021) - Wilden, Johanna; Yang, Fan; Günther, Gerrit; Russina, Margarita; Kuball, Alexander; Busch, Ralf; Meyer, Andreas
Abstract: The Ni self-diffusion in glass forming Pd40 Ni40 S20, Pd37 Ni37 S26 and Pd31 Ni42 S27 melts was probed by incoherent, quasielastic neutron scattering over a temperature range between 773 and 1023 K. The Ni self-diffusion coefficients are on a 10 −10  m 2  s −1 –10 −9  m 2  s −1 scale and barely change with composition. Each composition exhibits an Arrhenius-type temperature dependence of the Ni self-diffusion coefficients, which results in activation energies ranging from E A = 348 ± 16 meV for Pd40 Ni40 S20 to E A = 387 ± 6 meV for Pd37 Ni37 S26 . The structural relaxation shows a stretched exponential behavior even far above the liquidus temperatures. In addition, the viscosity of the Pd37 Ni37 S26 melt was measured under reduced gravity conditions. The diffusion calculated from the viscosity reveals a significant deviation from the measured Ni self-diffusion by a factor between 4 and 8. This may indicate a dynamic decoupling between the atoms within the Pd–Ni–S equilibrium melts.